FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI DI KABUPATEN MALANG PADA TAHUN 2010-2016 - Nur Kholis; Muhammad Faisal Abdullah (Jurnal Ilmu Ekonomi JIE, 2017)
This study aims to determine the influence of rice production on regency of Malang. The data collection in this research is secondary data. Data obtained from the relevant authorities, namely: Badan Pusat Statistik  (BPS). The analytical tool in this study is regression panel data. The hypothesis processed by F test, t test, and the coefficient of determination (R2) at the level of error is α = 5%.The dependent variable is the independent variable of rice production and the area of land, the cost of fertilizer and labor. Based upon the results of the study show that (X1) land area of positive and significant impact on rice production (Y), (X2) fertilizer significant negative effect on rice production (Y) and labor (X3) positive and significant impact on rice production (Y).Thus the results of this study are expected to be useful in compiling the policies and strategies effectively and efficiently to the activities for increasing rice production in Malang, East Java. Keywords: Land, Fertilizer Costs, Labor and Rice Production.